(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2025)
Age estimation by the use of X-rays is an age-old method of identification. However, there can be variations depending upon various factors such as age, an individual’s genetic makeup, diet, geographical habitat, and so on. Creating a regional database is need of the hour-rays of the elbow joints of individuals of Gujarat were studied by using Microsoft Office Picture Manager 2010 version for the appearance of ossification centers and epiphyseal fusion in the Department of Forensic Medicine and Department of Radio-diagnosis at a Medical College in Ahmedabad, Gujarat after the approval from Institutional Ethics Committee. All the findings showed a statistically significant association between age groups and the appearance of ossification centers and epiphyseal fusion. The study’s findings are discussed and compared to previous studies by authors from the Indian sub-continent &foreign. The persistence of epiphyseal scar on some bones may be influenced by factors other than chronological age.